Focus on Over-the-Counter Drugs' Misuse: A Systematic Review on Antihistamines, Cough Medicines, and Decongestants - Schifano, Fabrizio; Chiappini, Stefania; Miuli, Andrea; Mosca, Alessio; Santovito, Maria Chiara; Corkery, John M.; Guirguis, Amira; Pettorruso, Mauro; Di Giannantonio, Massimo; Martinotti, Giovanni (Frontiers in Psychiatry, 2021)
Background: Over the past 20 years or so the drug misuse scenario has seen the emergence of both prescription-only and over-the-counter (OTC) medications being reported as ingested for recreational purposes. OTC drugs such as antihistamines, cough/cold medications and decongestants, are reportedly the most popular in being diverted and misused. Objective: Whilst the current related knowledge is limited, the aim was here to examine the published clinical data on OTC misuse, focusing on: antihistamines (e.g., diphenhydramine, promethazine, chlorpheniramine, and dimenhydrinate); dextromethorphan (DXM)- and codeine-based cough medicines; and the nasal decongestant pseudoephedrine. Methods: A systematic literature review was carried out with the help of Scopus; Web of Science databases; and the related grey literature. For data gathering purposes, both the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and PROSPERO guidelines were followed (PROSPERO identification code CRD42020209261). Results: After completion of the selection, eligibility and screening phases, some 92 articles were here taken into consideration; case reports, surveys, and retrospective case series analyses were included. Findings were organised according to the specific OTC recorded. Most articles focussed here on DXM (n=54) and diphenhydramine (n=12). When specified, dosages, route(s) of administration, toxicity symptoms (including both physical and psychiatric ones), and outcomes were here reported. Conclusion: Results from the systematic review showed that the OTC misusing issues are both widespread worldwide and popular; vulnerable categories include adolescents and young adults, although real prevalence figures remain unknown, due to a lack of appropriate monitoring systems. Considering the potential, and at times serious, adverse effects associated with OTC misusing issues, healthcare professionals should be vigilant and ad hoc preventative actions should be designed and implemented.